Modern apostles of missionary byways - Thompson, A. C. 1812-1901.; Walsh, W. Pakenham 1820-1902.; Humphrey, Simon James 1820-1906.; Beach, Harlan P. 1854-1933.; Child, Abbie B.; Pierson, Arthur T. 1837-1911.; Princeton Theological Seminary (New York Student Volunteer Movement for Foreign Missions, 1899)
Hans Egede, Greenland's viking pioneer, 1686-1758, by A. C. Thompson.--Captain Allen Gardiner, R. N., "Pioneer to the most abandoned heathen", by W. P. Walsh.--Titus Coan, the St. Peter of Hawaii, 1801-1882, by S. J. Humphrey.--James Gilmour, "Brave" missionary to the Mongols, 1843-1891, by H. P. Beach.--Miss Eliza Agnew, Ceylon's "Mother of a thousand daughters", 1807-1883, by A. B. Child.--The Hon. Ion Keith-Falconer, pioneer in Arabia, 1856-1887, by A. T. Pierson.
Bibliography: p. 97-101
Keywords: Egede, Hans -- 1686-1758; Gardiner, Allen Francis -- 1794-1851; Coan, Titus -- 1801-1882; Gilmour, James -- 1843-1891; Agnew, Eliza -- 1807-1883; Keith-Falconer, I. G. N -- 1856-1887; Missions